Adaptive treatment strategies for children and adolescents with Obsessive-Compulsive Disorder: A sequential multiple assignment randomized trial. (August 2018) - Fatori, Daniel; de Bragança Pereira, Carlos Alberto; Asbahr, Fernando R.; Requena, Guaraci; Alvarenga, Pedro G.; de Mathis, Maria Alice; Rohde, Luis A.; Leckman, James F.; March, John S.; Polanczyk, Guilherme V.; Miguel, Eurípedes C.; Shavitt, Roseli G.
Highlights: Among the 40 children randomized to FLX who completed the first stage 41.7% responded to treatment. Among the 43 children randomized to GCBT who completed the first stage, 51.4% responded to treatment. To start the treatment with either FLX or GCBT and to switch to or add the other treatment led to similar rates of improvement. Provision of treatment for childhood OCD could be tailored according to the availability of local resources. Abstract: Objective: This sequential multiple assignment randomized trial (SMART) tested the effect of beginning treatment of childhood OCD with fluoxetine (FLX) or group cognitive-behavioral therapy (GCBT) accounting for treatment failures over time. Methods: A two-stage, 28-week SMART was conducted with 83 children and adolescents with OCD. Participants were randomly allocated to GCBT or FLX for 14 weeks. Responders to the initial treatment remained in the same regimen for additional 14 weeks. Non-responders, defined by less than 50% reduction in baseline Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) scores, were re-randomized to either switch to or add the other treatment. Assessments were performed at baseline, 7, 14, 21, and 28 weeks. Results: Among the 43 children randomized to FLX who completed the first stage, 15 (41.7%) responded to treatment and 21 non-responders were randomized to switch to (N = 9) or add GCBT (N = 12). Among the 40 children randomized to GCBT who completed the first stage, 18 (51.4%) responded to treatment and 17 non-responders were randomized to switch to (N = 9) or add FLX (N = 8). Primary analysis showed that significant improvement occurred in children initially treated with either FLX or GCBT. Each time point was statistically significant, showing a linear trend of symptom reduction. Effect sizes were large within (0.76–0.78) and small between (-0.05) groups. Conclusions: Fluoxetine and GCBT are similarly effective initial treatments for childhood OCD considering treatment failures over time. Consequently, provision of treatment for childhood OCD could be tailored according to the availability of local resources.